Antibiotic Resistance in Enterococcus faecalis Isolated from Hospitalized Patients - Esrafil Balaei Gajan; Adileh Shirmohammadi; Mohammad Aghazadeh; Mohammad Alizadeh; Alireza Sighari Deljavan; Farzin Ahmadpour (Tabriz University of Medical Sciences, 2013)
Background and aims. Enterococci are Gram-positive cocci that often occur in pairs (diplococci) or short chains. Beside developing high level of antibiotic resistance, these bacteria can cause wide range of disease in human, thus to help provide an effective treatment for infections caused by this genus, this study was conceived to provide information on Enterococcus faecalis Antibiotic resistance to widely used antibiotics in hospitalized patients. Materials and methods. Disk diffusion agar and Broth dilution methods were used to perform Antibiogram test on isolated Enterococcus faecalis. Culture medium used for Disk diffusion agar test was Muller Hinton agar, and for Broth dilution methods, Muller Hinton broth culture medium was utilized. In disk diffusion agar method, different commercial antibiotics disks produced by Pharmaceutical companies were used. Microsoft Excel software was used to perform statistical analysis. Results. Based on antibiograms of 105 cases, a high resistance to Synercid, Nalidixic acid, Oxacillin and Teofilin was detected whereas the lowest resistance observed in Nitrofurantoin, Vancomycin, Linezolid and Teicoplanin antibiotics. Conclusion. According to the results, Teicoplanin, Vancomycin, Linezolid and Nitrofurantoin are recommended against E. faecalis species